POSISI AKADEMIK PENDIDIKAN KEWARGANEGARAAN (PKn) DAN MUATAN/MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN (PPKn) DALAM KONTEKS SISTEM PENDIDIKAN NASIONAL - Udin S. Winataputra (Universitas PGRI Kanjuruhan Malang, 2016)
Epistemologically civic/citizenship education studies has been accentuated by continuous discoursesÃ‚Â on the ideals, instrumentation, and praxis of educating citizens for democratic citizenship. It was idealised by collective awarenes and committment of govement and civic educators community to substantiate the ideas of education for citizenship. It has also to beÃ‚Â the case for Indonesian citizenship/civic education. To be noted that along its six decades of educational history since 1946 it has been continually functioned as a vehicle for character building. This article briefly present a recent conceptual discourses dealing with learning outcomes of civic education for the next Indonesian 2045 era. It is encouraged that further discourses would firstly, enriched the state of the art of Pancasila and Civic Education, and secondly to reconvince its status within the Indonesia curriculum system.